2012
DOI: 10.1371/journal.pone.0035627
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ocular Scarring Post Glaucoma Filtration Surgery Using the Inflammatory Cell and Platelet Binding Modulator Saratin in a Rabbit Model

Abstract: Clinical RelevanceLate complications can occur with use of current antimetabolites to prevent scarring following glaucoma filtration surgery (GFS). Safer, more targeted, anti-fibrosis agents are sought.ObjectivesThe protein saratin has been shown to exhibit anti-fibrotic and anti-thrombotic properties in response to injury, but had not been used for glaucoma surgery. The goal of this study was to compare the efficacy of saratin with that of the widely accepted mitomycin-C (MMC) in prolonging bleb survival foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The recombinant Saratin was obtained in yeasts (Hansenula polymorpha) [104] and it is being commercialized by BioVascular which has developed this product to GMP standards and is evaluating the effects in clinical studies [105]. To date, in the literature, only a few animal studies have been published, where it has been given alone or together with other drugs in glaucoma rabbit models [106,107]. Saratin, when administrated alone in rat carotid endarterectomy model, significantly decreased platelet adhesion, intimal hyperplasia, luminal stenosis, and thrombosis.…”
Section: Other Inhibitors Of Factor Xamentioning
confidence: 99%
“…The recombinant Saratin was obtained in yeasts (Hansenula polymorpha) [104] and it is being commercialized by BioVascular which has developed this product to GMP standards and is evaluating the effects in clinical studies [105]. To date, in the literature, only a few animal studies have been published, where it has been given alone or together with other drugs in glaucoma rabbit models [106,107]. Saratin, when administrated alone in rat carotid endarterectomy model, significantly decreased platelet adhesion, intimal hyperplasia, luminal stenosis, and thrombosis.…”
Section: Other Inhibitors Of Factor Xamentioning
confidence: 99%
“…It is also noted that results from an animal study may not be directly applicable to human patients. The New Zealand rabbit is, however, an established model for evaluation of glaucoma surgery [10,17,18,26]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of TGF-b showed promise in animal models, but a clinical study found that a monoclonal antibody (CAT-152) was not effective at preventing trabeculectomy failure [13]. Preliminary studies investigating anti-transforming growth factor b2 (anti-TGF-b2), anti-vascular endothelial growth factor (anti-VEGF), anti-placental growth factor (anti-PIGF), inhibitors of platelet collagen interaction (saratin), and application of amniotic membrane have all shown success, but have not expanded to clinical trials [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Other reports indicated survival rate ranged from 0% to 50% at various follow-up periods (from 4-6 weeks). 16,[37][38][39] From these results, it appears to be difficult to achieve greater than 90% bleb survival (human 1-year goal) at 3 months in a rabbit model of filtration surgery with MMC, because the wound healing reaction is more aggressive in rabbits than in humans. Accordingly, the results of experiment 2 indicate that a HPF with 0.5 lg PTX provided sustained IOP reduction and favorable bleb survival even after a long follow-up period.…”
Section: Discussionmentioning
confidence: 99%